Comparison of Acute Physiology and Chronic Health Evaluation II, Bedside Index for Severity in Acute Pancreatitis and Modified Computed Tomography Severity Index Scores in Predicting the Outcome in Acute Pancreatitis in a Tertiary Care Centre in Nepal - Pandey, Rajesh; Pathak, Rahul; Jha, Anurag; Gnawali, Arun; Koirala, Dinesh (Journal of Nepal Health Research Council, 2023)
Background: It is important to identify the severity of acute pancreatitis in the early course of the disease. Methods: This prospective observational study included 83 patients with acute pancreatitis. The Acute Physiology and Chronic Health Evaluation II and the Bedside Index for Severity in Acute Pancreatitis scores were assessed within 24?hours of admission, and the modified computed tomography severity index score was calculated in those patients who underwent contrast enhanced computed tomography. The sensitivity, specificity, positive predictive value, and negative predictive value of scoring systems were calculated. The area under the curve was calculated for assessing the prognostic value of scoring systems. Results: The modified computed tomography severity index was the most accurate score in predicting severity and local complications with an area under the curve of 0.92 and 0.91, respectively. The Bedside Index for Severity in Acute Pancreatitis score was the most accurate in predicting organ failure and the need for intensive care unit admission with an area under the curve of 0.70 and 0.78 respectively. Conclusions: The results of this study demonstrate that modified computed tomography severity index and Bedside Index for Severity in Acute Pancreatitis scores had overall better predictive value than the Acute Physiology and Chronic Health Evaluation II score in predicting severity, organ failure, local complication, and need for intensive care unit admission. Keywords: Acute pancreatitis; APACHE II; BISAP; modified CTSI